Tribute to Michel E. Safar (1937–2024): A Groundbreaker in the Concept of Hypertension - Patrick Lacolley; Harry Struijker-Boudier; Veronique Regnault; Moyra Barbier (Artery Research)
Abstract The authors present a short review of the personality, clinical and scientific contributions of a distinguished member of our Academy, the Artery Society and so many others, where he contributed landmark advances in many fields of arterial function and cardiovascular risk. The Editorial Board of the Artery Research Journal and the Executive Committee of the Artery Society present their due respects to Prof. Michel Safar.